Epidemiological and clinical aspects of Trichophyton mentagrophytes/Trichophyton interdigitale infections in the Zurich area: a retrospective study using genotyping. (3rd February 2021) - Klinger, M.; Theiler, M.; Bosshard, P.P.
Abstract: Background: Trichophyton mentagrophytes (formerly Arthroderma vanbreuseghemii ) and its clonal offshoot Trichophyton interdigitale, which are leading causes of dermatophytoses, have recently been recognized as two separate species. Over the last 20 years, several internal transcribed spacer (ITS) genotypes of Trichophyton mentagrophytes and Trichophyton interdigitale have been identified, some of which have specific characteristics and lead to typical clinical manifestations. Objectives: The aim of this study was to determine the current epidemiology of Trichophyton mentagrophytes and Trichophyton interdigitale genotypes in Switzerland, particularly in the Zurich area. Methods: Consecutive cases diagnosed by ITS sequencing between 2009 and 2019 were retrospectively analysed. Results: A total of 81 Trichophyton mentagrophytes and 81 Trichophyton interdigitale cases were investigated. T. mentagrophytes infections clearly differed from T. interdigitale infections by affecting younger and more frequently female patients, targeting almost exclusively head and body rather than feet and toenails, leading to inflammatory dermatophytosis and often requiring a combination of systemic and topical treatment. Seven different T. mentagrophytes genotypes (II*, III, III*, IV, VII, VIII and XXVI) were observed, with genotype XXVI being discovered in this study. Genotype III occurred most frequently (56% of all T. mentagrophytes cases) and affected predominantly children. Genotypes III* and VII led to inflammatory tinea in most cases. Four strains that proved to be terbinafine resistant belonged to the 'Indian genotype' VIII, which mostly caused tinea glutealis and inguinalis. Conclusion: Being able to distinguish between Trichophyton mentagrophytes and Trichophyton interdigitale is of paramount importance as the two species cause different clinical presentations. In addition, ITS genotyping allows recognizing sources of infection and potential terbinafine resistance. The latter needs to be confirmed by resistance testing or by sequencing part of the squalene epoxidase (SQLE) gene.